Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Bus Berdasarkan Uji Kir Menggunakan Metode Promethee II (Studi Kasus: Dinas Perhubungan Provinsi Sumatera Utara) - Supirman Supirman; Murdani Murdani (STMIK Budi Darma, 2020)
One of the requirements for a bus / public transportation to be able to operate is passing the test carried out by the Transportation Department. The results of the transportation feasibility test still use manual calculations, while many transports do the daily test. Therefore a decision support system is needed to determine the feasibility of the bus based on the kir test. This study aims to determine the feasibility of the bus based on the left test. A decent bus will get a roadworthiness certificate issued by the Transportation Agency. In testing, good planning management is needed, one of which is by determining the feasibility. This decision support system can determine the calculated value of all criteria. This system uses the Promethee II method. In this case the Promethee II method can determine the priority of the bus driver test based on the highest value. Thus this system is able to shorten the bus verification process at the North Sumatra Provincial Transportation Office, thus helping testers determine which buses are worthy of road